Influência do polimorfismo R577X do gene ACTN3 no processo de aclimatação à alta altitude - Bottura, Ricardo Muller [UNIFESP] (2019)
Introduction: Hypoxemia is the decrease in arterial blood saturation. This condition leads the organism to adjust the various metabolic processes in an attempt to establish better oxygenation to the tissues. During this process, called acclimatization, it is normal to present mood and cognition disturbances or to develop some symptoms that can lead to mountain sickness. However, not everyone has such symptoms or alterations and individuals from high altitude regions present genetic differences in relation to low altitude natives that can contribute to a better adaptation of the acute form. One of these differences is the greater proportion of type I muscle fibers, which may originate from the R577X polymorphism of the ACTN3 gene. Objective: The objective of this study was to compare the response of individuals with different ACTN3 genotypes at simulated altitude at 4500m on cognition, mood and the presence of symptoms of Acute Mountain Sickness (AMS). Methods: Twenty-three volunteers (RR = 7, RX = 8, XX = 8) spent four hours exposed to a simulated altitude of 4,500 m inside a normobaric hypoxia chamber, where the concentrations of lactate and glucose, SpO2, FC, reaction time, the mood state, and the symptoms of AMS. All analyzes were done immediately before entering the chamber and at each hour of exposure. Statistical analysis was performed using the IBM SPSS Statistics 21 software. Results: Our results point to an association between the symptoms of AMS and the presence of the R allele of the R577X polymorphism. This may be related to a greater dependence on glucose metabolism, since the RR and RX groups showed lower glycemia than the XX group after 4 hours of exposure at 4500m altitude. There was no difference between groups for Mood and Reaction Time. Conclusion: We conclude that individuals with at least one R allele of the R577X polymorphism are more susceptible to the effects of hypoxia during the acclimation process and may present the symptoms of AMS.